At the table with the big three carnivores - a sympatric occurrence of the golden jackal with bear, wolf and lynx captured on a camera trap in Slovakia - Guimaraes, Nuno; Bučko, Jozef; Slamka, Marián (European Journal of Ecology, 2021)
In last decades, golden jackals expanded significantly their distribution range, increasing their population density, being nowadays present in many countries in Europe. In Slovakia, their dispersion and population increase became more constant from 2009. Records of wolves, lynx and bear from camera traps are rather common across Slovakia, while those of golden jackals are still rare, despite a large number of active traps. In this work, we present records of a camera-trap, located on the east side of the Kysuce Protected Landscape Area, where, for the first time, we detect a sympatric occurrence of the golden jackal with all three native large carnivores.